2018
DOI: 10.15845/voices.v18i4.2600
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Bonds between Children, Young People, and their Families after Family Violence

Abstract: The experience of family violence greatly impacts family dynamics and often results in children and young people becoming intertwined in a complex cycle of love, hope, and fear within their family system. Research in this context has emphasised how having a close relationship to an attuned adult or caregiver is a key protective factor for children and young people experiencing family violence, therefore engagement of family and supportive systems is an important part of the work. This article will explore our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…However, because clients in the current study were engaged in both individual and family counseling, they were able to gain insights into themselves and their families, while learning to more effectively communicate with one another. Individual sessions provided the children safety for self-exploration (Fairchild & Sheridan, 2018), and insights that occurred during individual counseling could then be harnessed in the family session, leading to changed family dynamics and communication patterns. Learning coping skills was part of this process and meaningful, as has also been found by Sackett and Cook (2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, because clients in the current study were engaged in both individual and family counseling, they were able to gain insights into themselves and their families, while learning to more effectively communicate with one another. Individual sessions provided the children safety for self-exploration (Fairchild & Sheridan, 2018), and insights that occurred during individual counseling could then be harnessed in the family session, leading to changed family dynamics and communication patterns. Learning coping skills was part of this process and meaningful, as has also been found by Sackett and Cook (2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, varying perspectives on who and to what degree each family member was to be included in the counseling have also existed (Cordell & Allen, 1997;Miller & McLeod, 2001;Sori & Sprenkle, 2004). One perspective was that young clients could best address specific treatment needs through the safe space of individual counseling (Fairchild & Sheridan, 2018), while they and their family members addressed issues of family dynamics in family counseling (Guerney & Guerney, 1987;Lund et al, 2002). In a metasynthesis of literature on treatment for children and families, Lund et al (2002) found that a combination of individual, family, or couples/parent counseling was a recommendation included in one fourth of all publications (N ¼ 60) examined.…”
Section: Employing Both Individual and Family Counselingmentioning
confidence: 99%
See 2 more Smart Citations
“…Uiteraard moet vermeden worden dat vormen van kindermishandeling kunnen voortduren in contact tussen ouders en kinderen. In dat geval kunnen andere, veilige, familieleden een bron van steun worden voor een kind (Fairchild & Sheridan, 2018).…”
Section: B R E a K D O W Nunclassified